2021
DOI: 10.5935/0034-7280.20210012
|View full text |Cite
|
Sign up to set email alerts
|

Multiple layers on the Descemet membrane

Abstract: Relato de caso não descrito na literatura oftalmológica nacional de múltiplas camadas da membrana de Descemet. Mulher de 59 anos, pseudofácica, com diagnóstico de ceratopatia bolhosa, foi submetida à ceratoplastia penetrante em olho direito, sendo encontrado achado incomum de multiplicidade de camadas da membrana de Descemet, variáveis em forma e espessura, além de corpos ovoides com coloração de metamina de prata de Gocott-Gomori (GMS) negativa. Como a membrana de Descemet tem no seu desenvolvimento um períod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Hypoglycemia is the most common metabolic alteration in newborn patients. In veterinary medicine, the puppies most likely to manifest hypoglycemia are neonates who have gone through stressful events such as hypoxia at birth, neonates born from hypoglycemic mothers, sick, orphaned, premature and low birth weight neonates (5,29,41). Table 1 shows the main risk factors for the development of neonatal hypoglycemia.…”
Section: Risk Factors For Neonatal Hypoglycemia In Dogsmentioning
confidence: 99%
See 4 more Smart Citations
“…Hypoglycemia is the most common metabolic alteration in newborn patients. In veterinary medicine, the puppies most likely to manifest hypoglycemia are neonates who have gone through stressful events such as hypoxia at birth, neonates born from hypoglycemic mothers, sick, orphaned, premature and low birth weight neonates (5,29,41). Table 1 shows the main risk factors for the development of neonatal hypoglycemia.…”
Section: Risk Factors For Neonatal Hypoglycemia In Dogsmentioning
confidence: 99%
“…In addition, systemic infections, such as neonatal sepsis, lead to rapid glucose consumption and increased risk of hypoglycemia (1,4,5,9,43,44). A study demonstrated that approximately 65% of neonates in sepsis develop hypoglycemia (41).…”
Section: Risk Factors For Neonatal Hypoglycemia In Dogsmentioning
confidence: 99%
See 3 more Smart Citations